(untitled) (World Economics and Finance Bulletin, 2022)
The research aims toShedding light on the nature of financial control and sustainable development in terms of dimensions and objectives.as well asLinking the observations of the Office of Financial Supervision to the dimensions and objectives of sustainable development and its relationship to industrial activityThe researchers reached a set of recommendations, including:The contribution of the activities of coke and refined petroleum products by (24%) by employing the workforce, followed by the activities of the other non-metallic minerals industry by (20.1%). They also found thatsustainable developmentMeansbalancesbetween thingsThe economic, social, environmental and institutional needs of the present and future generations on the other hand. And therefore deduceThe weak performance of the Ministry of Industry in contributing to the achievement of the sustainable development goals (eighth and ninth) and the eighth goal represented in: developing steady, comprehensive and sustainable economic growth for all, full and productive employment, and providing decent work for all, and its goal (developing efficiency in the use of global resources in the field of consumption and production), And the ninth goal: which includes encouraging inclusive and sustainable industrialization for all, and encouraging innovation, and its goal is (the development of inclusive and sustainable industrialization).